2000
DOI: 10.1007/s101940070026
|View full text |Cite
|
Sign up to set email alerts
|

Stress and chronic headache

Abstract: IntroductionIt is a matter of clinical experience that psychological factors, in particular stress, can exert notable effects on primary headaches. Several studies have shown that stress is one of the most common trigger factors for headache, both in migraine and in tension-type headache [1][2][3][4][5]. It is reasonable, therefore, that stress may exert effects on the clinical evolution of these headaches. For example, stressful events may increase headache frequency or promote transformation of an episodic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Furthermore, most daily headache sufferers have a history of episodic migraine and at least some of their current attacks have the characteristics of migraine. For these reasons it has been suggested that chronic daily headache may be a transformation of migraine 10–14 . Several names and diagnostic criteria have been proposed for these frequent headaches 11–13,15,16 .…”
mentioning
confidence: 99%
“…Furthermore, most daily headache sufferers have a history of episodic migraine and at least some of their current attacks have the characteristics of migraine. For these reasons it has been suggested that chronic daily headache may be a transformation of migraine 10–14 . Several names and diagnostic criteria have been proposed for these frequent headaches 11–13,15,16 .…”
mentioning
confidence: 99%
“…The term chronic daily headache is currently used to refer to headaches that occur 15 or more days per month at least 4 hours a day, 6 but it is not included in the International Headache Society (IHS) classification of headache disorders 7 . Further, many different terms have been used to refer to those forms of chronic headache that appear to have evolved from episodic migraine: transformed migraine, evolutive migraine, chronic daily migraine, mixed headache, chronic migraine, and migraine with interparoxysmal headache 8–12 …”
mentioning
confidence: 99%
“…Other limitations of pharmacological therapies include the high cost associated with on-going medication, contraindications and medication intolerance. 9 While medication is the mainstay of treatment, psychological comorbidity is common in individuals with chronic headache or migraine, 10 with a variety of functions such as sleep (fatigue-related problems) and activities such as exercise and emotional experience (stress-related problems) affected. 8 In addition, it has been found that the anticipation of a headache can cause significant anxiety between episodes 1 and that depression may be three times more common in individuals experiencing severe headaches or migraines than in headache-free individuals, 5 although estimates may be unreliable.…”
mentioning
confidence: 99%